1998
DOI: 10.1152/jappl.1998.84.4.1311
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced insulin resistance precedes other aspects of the metabolic syndrome

Abstract: This study was designed to examine the effects of a high-fat refined-sugar (HFS) or a low-fat complex-carbohydrate (LFCC) diet on insulin-stimulated skeletal muscle glucose transport, plasma insulin, blood pressure, plasma triglycerides, plasma glycerol, body weight, and body fat in female Fischer rats. Insulin-stimulated glucose transport was significantly reduced in the HFS group at 2 wk, 2 mo, and 2 yr, whereas serum insulin was significantly elevated at all time points. Blood pressure was not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
131
2
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 51 publications
16
131
2
6
Order By: Relevance
“…Therefore, an inability to suppress a gluconeogenic enzyme by insulin can initiate many of the disorders associated with syndrome X supporting the hypothesis that insulin resistance can trigger syndrome X. Consumption of a high-fat cafeteria diet caused a more dramatic manifestation of syndrome X probably because high-fat diets induce more severe insulin resistance [14,16]. Our data were indicative of this, showing fasting insulin values three times higher than normal values and hyperglycaemia after eating cafeteria food.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, an inability to suppress a gluconeogenic enzyme by insulin can initiate many of the disorders associated with syndrome X supporting the hypothesis that insulin resistance can trigger syndrome X. Consumption of a high-fat cafeteria diet caused a more dramatic manifestation of syndrome X probably because high-fat diets induce more severe insulin resistance [14,16]. Our data were indicative of this, showing fasting insulin values three times higher than normal values and hyperglycaemia after eating cafeteria food.…”
Section: Discussionsupporting
confidence: 78%
“…Our data were indicative of this, showing fasting insulin values three times higher than normal values and hyperglycaemia after eating cafeteria food. Others have shown that a high-fat, refined sugar diet can induce insulin resistance and hyperinsulinaemia in Fischer rats after only 2 weeks, followed by hypertriglyceridaemia at 2 months, obesity at 5 months, and hypertension at 12 months [14] illustrating, as we have, that insulin resistance independent of obesity can be the underlying cause of syndrome X. This is also supported by studies in non-obese, insulin-resistant mice lacking insulin receptor substrate-1 (IRS-1) which develop hypertriglyceridaemia and hypertension [26].…”
Section: Discussionmentioning
confidence: 99%
“…We chose this experimental rat model based on our previous results, and literature data (Barnard et al 1998, Obradovic et al 2015b). All metabolic parameters for these rats in response to the treatments administered in this study are detailed in our previous study (Obradovic et al 2015a).…”
Section: Animals and Experimental Treatmentmentioning
confidence: 99%
“…In our study, we used male rats fed a HF diet as a model of obesity-associated IR. In this model the HF diet induces whole body IR/hyperinsulinemia, endothelial dysfunction and hypertension (Barnard et al 1998, Panchal et al 2011. Furthermore, we have previously demonstrated using the same male model rats, that a HF diet applied for 10 weeks induces obesity accompanied with abnormalities such as cardiac hypertrophy, increased serum insulin concentration, whole body IR, hyperlipidaemia, hyperleptinemia and inflammation (Obradovic et al 2015a, Obradovic et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…In Tehran, Iran, it has been estimated to occur in Ͼ30% of adults (5), a prevalence significantly higher than that of most developed countries (6). In choosing a therapeutic diet for metabolic syndrome, all the abnormalities of the metabolic syndrome should be taken into account (7,8). Most patients with the metabolic syndrome are overweight or obese, especially upper-body obese (9,10).…”
mentioning
confidence: 99%